The Effects of Resistance Training on Body and Liver Fat Stores and Insulin Resistance in Peoples with Non-Alcoholic Fatty Liver Disease - Mohammad Ebrahim GHAMAR CHEHREH; Alireza SHAMSODDINI; Mostafa RAHIMI (Tehran University of Medical Sciences, 2020)
No Abstract